Room temperature synthesis of pillared-layer metal–organic frameworks (MOFs). Issue 50 (14th November 2022) - Habtemariam, Tesfaye Haile; Raju, V. J. T.; Chebude, Yonas
Abstract : A strategy for the production of water stable pillared-layer MOFs in less toxic solvents and potentially in large amounts. Abstract : A pillared-layer MOF, [Cu2 (Fu)2 (BPY)]·H2 O n, was synthesized at room temperature employing a mixture of water and methanol as the reaction solvent. By using the sodium salts of fumarate, instead of the native acids, the target MOF could be readily prepared in aqueous media. The PXRD of this MOF was found to be in good agreement with the simulated diffractogram from single crystal data of related MOF made at a higher temperature using DMF as the solvent. In addition to characterization by PXRD, TGA, and ESEM, N2 -sorption measurements revealed the formation of mesopores in the MOF's structure under study. The electronic band gap and magnetic properties of this pillared-layer MOF were also studied.